2017
DOI: 10.1039/c7py00908a
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly and functionalization of alternating copolymer vesicles

Abstract: This work reports novel alternating copolymer vesicles and their facile functionalization with carboxyl and amino groups through click copolymerization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 63 publications
2
38
0
Order By: Relevance
“…First, the polymerization process is very simple just by using DA directly with no need of further modification, and the click polymerization is fast and almost quantitative. [ 29–32 ] On the contrary, in the reported CFPs, polymerizable groups like double bonds should be incorporated into catechol structures first before polymerization. [ 33 ] Second, the alternating structure enables the polymers with high catechol content (50% molar ratio) and regular catechol sequence, which are beneficial to the isotropic adhesion.…”
Section: Methodsmentioning
confidence: 99%
“…First, the polymerization process is very simple just by using DA directly with no need of further modification, and the click polymerization is fast and almost quantitative. [ 29–32 ] On the contrary, in the reported CFPs, polymerizable groups like double bonds should be incorporated into catechol structures first before polymerization. [ 33 ] Second, the alternating structure enables the polymers with high catechol content (50% molar ratio) and regular catechol sequence, which are beneficial to the isotropic adhesion.…”
Section: Methodsmentioning
confidence: 99%
“…This kind of stacking manner seems to be typical in the amphiphilic ACP assemblies. Our research showed that the amphiphilic ACPs could self‐assemble into vesicles, whereas the polymeric chains stacking in the membranes of these vesicles also arranged in a similar manner . Details of the process and the corresponding results are shown in Figure .…”
Section: Self‐assembly Of Amphiphilic Acpsmentioning
confidence: 99%
“…Our research showedthat the amphiphilic ACPs could self-assemble into vesicles, whereas the polymeric chainss tacking in them embranes of these vesiclesa lso arrangedi nasimilarm anner. [17] Details of the process and the correspondingr esultsa re shown in Figure 4. As demonstrated by Figure 4a,P (DHO-a-DHBDT) was firstly synthesized by click copolymerization between the DHBDTand ODE monomers.…”
Section: Self-assembly Of Amphiphilic Acpsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the control experiments,two samples of amino vesicles and amino RBCs were prepared (Supporting Information, Figures S19-S21). [13] In the same amino concentrations with amino-SUAs,t he capture efficiencies of amino-vesicles and amino-RBCs with FITC-BSA (7.14 nm)a re 7.31 %a nd 31.1 %, respectively. Evidently,t he complex structure of SUAs with aR BC core and many radiating tubular spines is also important for the high protein capture efficiencya tu ltra-low concentration.…”
mentioning
confidence: 94%